PENERAPAN PERMAINAN TOM AND JERRY DALAM MENINGKATKAN HASIL BELAJAR LOMPAT JAUH (Department of Physical Education, Sport, Health and Recreation, 2013)
This research method is action research (PTK) through several cycles with the first cycle andsecond cycle with the research steps are: (1) a preliminary investigation and collection of information,including field observations and literature review, (2) planning by reviewing learningmaterials are long jump, exercising plan learning (RPP) in accordance with predeterminedindicators, preparing props, set pieces of student evaluations. (3) action, is the implementationof the learning process whereby researchers express purpose of learning in students, aswell as delivering learning modell will be implemented. (4) observations, researchers carry outobservations of the students during the learning process, and record the results. (5) reflection,this step is carried out after the end of learning process where researchers evaluate the learningprocess of the next cycle, planning further action planning for the second cycle. In this study,researchers used the fourth grade students of SD Negeri Turitempel Guntur District Demakmany as 32 students. The data analysis technique used is descriptive percentages to uncoverthe cognitive, psychomotor, and affective student after using the product. Hasi lpenelitian ofthe data obtained in the first cycle at the first meeting by 17 students (53.15%) have not beencompleted and 15 students (46.88%) completed and the second meeting by 4 students (12.50%)have not been completed and as many as 28 students(87.50%)completed.